Birth Asphyxia, Cerebral Metabolism and Head Size - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Studies of cerebral oxidative metabolism were carried out by phosphorus magnetic resonance spectroscopy during the first week of life in 52 infants with birth asphyxia admitted to the Neonatal Unit at University College Hospital, London.